Urban Food Environments and Diets (UFED) food environment assessment guidance - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This guidance document is linked to the UFED web tool and meant to be shared in conjunction with use of an online decision-making tool for planning dietary and food environment assessments in urban and peri-urban areas.